Tren Healing di Instagram: Penyembuhan Kekinian di Kalangan Mahasiswa - Halijah, Nur (Emik, 2023)
Healing has become a trended term on Instagram since Covid-19. In 2022, there were a sharp increase of searching for the word “healing” in the Google search engine as compared to 2021. The search for “healing” itself refers more to healing in the sense of traveling, which include holiday. This is due to the fact that during Covid-19 pandemic people stayed at home which caused boredom and stress, so it needs some kind of refresh, popularly known as healing. While most of literatures on healing focus more on the impact of healing, the novel contribution of this article is the importance of posting students’ healing activities in social media. This study was conducted virtually through Instagram since healing caption and healing hashtags (#healing) are widely posted on Instagram. There were 12 students involved in this study, consisting of seven women and five men, whose age ranges between 18 and 21 years, and who are quite active and intensive in healing and posting them on Instagram. Data was collected using interview through chatting and voice note in Instagram and Whatsapp; and observation was carried out by searching for and following #healing. The study shows that healing means the process of curing. In current practice, students interpret healing as: (1) taking a break from activities that cause stress (2) taking a vacation to reduce psychological burden; and (3) “sedative” from various mental tensions. The way they interpret healing is reflected in the healing-related activities they undertake. They are hang-outing in coffee shops/cafés with friends, climbing cool mountains, enjoying the beauty of the beach, exercising, or motorbiking without a clear destination or going to places that can soothe the soul. In essence, whatever activity is carried out for recuperation, this can be categorized as healing. The underlying reason for students to post their healing activities is to promote tourist destinations; as a platform for expressing oneself; and to save immortalized moments considering that Instagram has its archiving facilities. Therefore, Instagram, in this context, is a platform to make this happen.